Curcumin-infused nanostructured lipid carriers: a promising strategy for enhancing skin regeneration and combating microbial infection - Ola Elkhateeb; Mohamed E. I. Badawy; Hossam G. Tohamy; Howaida Abou-Ahmed; Mahmoud El-Kammar; Hoda Elkhenany (BMC Veterinary Research, 2023)
Abstract Background Curcumin is a biomolecule that can be extracted from the Curcuma longa that has been shown to have the potential to aid skin wound healing. It has been studied for its anti-inflammatory and antioxidant properties, which may help to reduce swelling and promote tissue repair. However, curcumin has low solubility in water, which can limit its absorption and bioavailability. Encapsulating it in lipid nanoparticles may help to increase its absorption, leading to improved bioavailability. Methods Curcumin-loaded nanostructure lipid nanocarriers (CURC-NLCs) were prepared and characterized. Also, the phenolic, flavonoid contents, antioxidant and antimicrobial efficacy against gram-positive and gram-negative bacteria were investigated. Furthermore, in vivo rabbit animal model was used to test its regenerative capacity and wound-healing efficiency. Results The CURC-NLCs significantly increased the content of phenolic and flavonoid compounds compared to curcumin, resulting in a dramatic increase in antioxidant activity. CURC-NLCs also showed a potent inhibitory effect on Gram-positive, Gram-negative, and fungi, two times higher than curcumin. CURC-NLCs showed a higher potential to fasten the wound healing of full-thickness skin injuries as it resulted in 1.15- and 1.9-fold higher wound closure at the first week of injury compared to curcumin and control, respectively (p < 0.0001). Conclusion These results suggest that CURC-NLCs have an excellent potential to promote skin regeneration, which could be attributed to its antioxidant and broad-spectrum antimicrobial effect.